Clinical and Epidemiological behavior of Acute Dentoalveolar Abscess in Patients of the Health Area VII in Cienfuegos - Ana Belkys Hernández Millán; Zenia Lizette Hernández Millán; Regla Martínez de la Cotera Molina; Mercedes Verónica Diego Cobelo; Diosky Ferrer Vilches; Nora Sexto Delgado (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Background: acute dentoalveolar abscess is a dental emergency and one of the major condition affecting the population; however, there are few studies on the subject. Objective: to describe the clinical and epidemiological characteristics of acute dentoalveolar abscess in patients of the health area VII in Cienfuegos. Methods: a descriptive study was conducted from January to December 2013 in the Health Area VII, Cienfuegos. The universe consisted of 672 patients and the sample included 374 individuals selected by simple random sampling. Primary data recording and data collection was obtained from medical records prior informed consent of the patients. The main variables were age, sex, pulp irritating agents. Results: females were more affected with 55, 35% and the 19-34 year age group with 33.69%. The main pulp irritator was microbial, 59.36%. Among the iatrogenic factors, the remains of decayed tissues were significant with 32.35%. Conclusions: there is a high number of patients with acute dentoalveolar abscess, thus, as a dental emergency, the dentist should know the characteristics and factors that develop the disease to promote a comprehensive job in terms of health promotion, prevention, treatment and rehabilitation of affected patients.